Cover Picture: Visible‐Light‐Assisted Selective Catalytic Reduction of Nitric Oxide with Ammonia over Dye‐Modified Titania Photocatalysts (ChemCatChem 12/2015). Issue 12 (15th June 2015) - Yamamoto, Akira; Teramura, Kentaro; Hosokawa, Saburo; Shishido, Tetsuya; Tanaka, Tsunehiro
<x xml:space="preserve">Abstract</x> The Front Cover picture shows a high‐performance photocatalyst for selective catalytic reduction of NOx with NH3 under visible light (photo‐SCR). In their Full Paper, A. Yamamoto et al. demonstrate the photo‐SCR under visible light by using dye‐sensitized TiO2 photocatalysts. Complete conversion of NO (>99%) and selectivity to N2 (>99%) were achieved over a Ru‐dye‐sensitized TiO2 photocatalyst even at a high gas hourly space velocity and at low temperatures. Based on a reactivity of surface species identified by DRIFT and UV/Vis spectroscopies, they proposed a reaction mechanism. The article highlighted by this cover can be found on p. 1818 ff. of Issue 12, 2015.